Effect of Welding Sequence and Constraint on the Residual Stress and Deformation of Thick Welded Butt Joint Made of Q345qD Steel - Yi Zhang; Wenxue Su; Hua Dong; Tao Li; Hongyou Cao (Advances in Civil Engineering)
In this paper, the residual stress and deformation of 32 mm thick welded butt joints made of Q345qD steel using gas metal arc welding (GMAW) are studied by using the thermoelastic-plastic finite element analysis (FEA). Element birth and death technique is used to simulate the deposition of the welding consumables, and the volume heat source in double-ellipsoidal distribution is used. An in-house python code is developed to enable the volume heat source movement. After the finite element model was verified against the experimental results, the effects of five welding sequences and two types of boundary constraint conditions on the residual stress and deformation of the thick welded butt joints were investigated. Results of the experimental measurement and the numerical simulation are in good agreement. The transverse residual stress and the vertical deformation can be significantly reduced by increasing the alternating times of the welding beads in two halves of the weld. The transverse residual stress and the vertical deformation can be reduced by 21.4% and 87.4%, respectively. In addition, the residual stress and deformation of the thick welded butt joints are significantly affected by the applied constraints. Increasing the constraint significantly increases the overall level of the transverse residual stress but can decrease the maximum longitudinal residual stress by 51.8% and the vertical deformation by 65.9%.